The binding nature of the opinions of the Supervisory Agency for State Procurement - Franco Arias, Billy (2015)
In the first part of this essay, the author describes the regulatory regime governing the issuance of opinions by the Supervising Agency of the Government Procurement (OSCE) in Peru. In the second, there is a series of interpretative elements of the binding nature of opinions of OSCE that were provided by the legislature and that institution. The third is a review of the doctrinarian characteristics that defined the institution of the Administrative Advisory Service. And finally, in the fourth part, the author proposes an interpretation of the meaning and scope of the binding nature of opinions of OSCE, with focus on their application across the various stages of government procurement in Peru.